2000
DOI: 10.1364/ao.39.000642
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum deposition of chiral sculptured thin films with high optical activity

Abstract: We present the technique of bideposition to realize thin-film helicoidal bianisotropic mediums (TFHBM's) that exhibit high optical activity. We show, by experiment as well as by simulation, that the optical rotation produced by these chiral sculptured thin films is roughly proportional to the square of the local linear birefringence. Experimental measurements on bideposited TFHBM's of titanium oxide yield a typical value of 5 degrees /mum for the effective specific rotation in the short-wavelength regime; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(82 citation statements)
references
References 30 publications
2
79
0
1
Order By: Relevance
“…As the birefringence increases, it would be anticipated that the discrepancy would increase further since then the inherent assumption in coupled wave theory, that |δn| <<n starts to break down. Hodgkinson et al [25] have achieved a relative birefringence of |δn|/n = 0.072 and we have found that the formulae still perform with about 5% maximal discrepancy in this case, the principal discrepancy being at the band edges, as is already apparent from Figs. 8 and 9.…”
Section: Comparison Of Methodssupporting
confidence: 75%
“…As the birefringence increases, it would be anticipated that the discrepancy would increase further since then the inherent assumption in coupled wave theory, that |δn| <<n starts to break down. Hodgkinson et al [25] have achieved a relative birefringence of |δn|/n = 0.072 and we have found that the formulae still perform with about 5% maximal discrepancy in this case, the principal discrepancy being at the band edges, as is already apparent from Figs. 8 and 9.…”
Section: Comparison Of Methodssupporting
confidence: 75%
“…of the Bragg regime is proportional to both the average refractive index,   as well as film half-pitch thickness, Ω and is calculated by using the equation,     Ω    [27,28]. The aim of the present work is to study the optical and structural properties of a bilayer circular filter realized by a two-layer TiO 2 helical film with layers of opposite structural handednesses.…”
Section: Introductionmentioning
confidence: 99%
“…The rod-shaped optically birefringent molecules within chiral liquid crystal (CLC) cells produce such structures [25]. Recent experimental effort led to nano fabrication of sculptured thin films, the solid-state analog to CLC cells [26][27][28][29]. The optical response of non-depolarizing DHTF structures is described by the so-called Jones matrix elements [10,25].…”
Section: Introductionmentioning
confidence: 99%